DEVELOPING REALISTIC MATHEMATICS EDUCATION-BASED WORKSHEETS FOR IMPROVING STUDENTS' CRITICAL THINKING SKILLS - Reza Lestari; Rully Charitas Indra Prahmana; Maureen Siew Fang Chong; Masitah Shahrill (Jurnal Infinity, 2023)
Applying critical thinking is an essential skill in the 21st century. However, teaching materials that do not facilitate students to improve these skills impact the achievement of learning objectives. Therefore, educators need appropriate teaching materials that encourage students to enhance their thinking skills. This study aims to develop teaching materials based on Realistic Mathematics Education (RME) to improve students’ critical thinking skills. The development model used is ADDIE consisting of Analysis, Design, Development, Implementation, and Evaluation phases. The instruments used, consist of validated student worksheets based on material experts and media experts, pretest questions, posttest questions, and the practicality of student worksheets. The results showed that the student worksheets developed were feasible regarding validity, practicality, and effectiveness. The validity of the student worksheets is indicated by the average score of two material expert validators and two media expert validators, each of which is in the good and excellent categories. The practicality of the student worksheets is denoted by the average value of student assessments included in the practical category. Then its effectiveness is shown by increasing students’ critical thinking skills after being given intervention using the student worksheets.